PEMILIHAN BAHASA JAWA-BAHASA INDONESIA OLEH PENUTUR ASLI BAHASA JAWA: STUDI KASUS PADA MASYARAKAT KARANG MALANG Suharyanto - Suharyanto NFN (Kibas Cenderawasih : Jurnal Ilmiah Kebahasaan dan Kesastraan, 2019)
This paper aims to know code choosing of Javanese-Indonesian for the family domain of Javanese native speaker at Karang Malang. Secondly, it is also purposes to analyze the impact of age on language choosing. This is a sociolinguistic research by quantitative method.There was a finding that the younger respondents tend to speak Indonesian more often. Thus, it is an indication of language infiltration from Indonesian to Javanese. The age factor on language choosing is supported by Analyzed of Variant .